Ensuring the accuracy of technological systems with aggregate-module configuration through the unification of base and clamping system elements - Pokhyl, Andrii (National Technical University "Kharkiv Polytechnic Institute", 2025)
The study analyzes the design features of machines with aggregate-module construction and explores the unification of grounding and clamping system elements. Modern aggregate technological machining systems (ATMS) prioritize flexibility and precision while maintaining cost-efficiency. This research proposes a model for designing positioning and clamping devices that supports structural reconfigurability and enhances processing accuracy. The findings emphasize the benefits of modular unification in improving technological performance, reducing design costs, and enabling rapid reconfiguration for diverse manufacturing needs.
Keywords: aggregate technological machining systems; unification; clamping systems; positioning devices; machining accuracy; modular design